Evaluasi Hasil Belajar sebagai Instrumen Peningkatan Mutu Pendidikan: Kajian Teoritis dan Praktis: Pendekatan Systematic Literature Review dalam Pendidikan - Simbolon, Christella Miranda Josephine; Simamora, Septy Idola; Sinaga, Emi Debora; Deni Adriani; Dalimunthe, Muhammad Bukhori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Evaluation of learning outcomes is a crucial component of the education system, playing a role in determining the quality of the learning process and outcomes. As educational paradigms evolve, evaluation no longer serves solely as a measure of academic achievement but also as a strategic instrument for continuously improving the quality of education. This study aims to analyze the role of evaluation of learning outcomes from theoretical and practical perspectives in efforts to improve the quality of education.The method used was a literature study using a Systematic Literature Review (SLR) approach, which involved collecting, selecting, and analyzing various relevant scientific sources. Data were analyzed using content analysis and narrative synthesis techniques to identify patterns, themes, and relationships between concepts.The study results indicate that evaluation of learning outcomes has shifted from a summative approach to a more formative, diagnostic, and holistic approach. Effective evaluation must be integrated into the learning process, encompassing cognitive, affective, and psychomotor aspects, and supported by the use of technology. Furthermore, a gap was identified between theoretical concepts and practice, particularly regarding educator competency and the administrative nature of evaluation implementation.Thus, evaluation of learning outcomes plays a strategic role in improving the quality of education if designed and implemented appropriately, systematically, and sustainably.